Development of a Module with a RME Approach on the Topic Systems of Linear Equations in Two Variables - Leni Agustina Daulay; Bettri Yustinaningrum; Feri Tiona Pasaribu; Sri Lestari Manurung; Elika Putri (AT-TA'LIM, 2025)
This research seeks to create legitimate and practical teaching materials in the form of a module utilizing a realistic mathematics education approach focused on the topic of systems of linear equations in two variables. This study utilizes the research and development (RD) approach, specifically the Thiagarajan 4-D model, which consists of four stages: (1) definition, (2) design, (3) development, and (4) dissemination. We conducted the research at MTsN 1 Central Aceh. Two classes, each with high and moderate abilities, participated in the research. The trial analysis yielded the following findings: (1) Validity, as two experts validated the teaching materials; (2) Practicality, as demonstrated by an average implementation of the learning syntax exceeding 75%, an average student activity exceeding 75%, extremely positive student and teacher responses to the module, and a classification of the developed module as practical. According to the results of the students' learning tests, 15 students completed the requirements out of 19 students in the high-ability class, and 14 students completed the requirements out of 19 students in the medium-ability class. Consequently, we categorize the percentage of students who have met the requirements as excellent. The module created utilizing a realistic mathematics education technique for the topic of systems of linear equations in two variables for eighth grade is deemed viable, indicating it is both valid and practical.